2004
DOI: 10.1242/jeb.01330
|View full text |Cite
|
Sign up to set email alerts
|

The tube cement of Phragmatopoma californica: a solid foam

Abstract: SUMMARY Phragmatopoma californica is a marine polychaete that builds protective tubes by joining bits of shell and sand grains with a secreted proteinaceous cement. The cement forms a solid foam (closed cells) via covalent crosslinking, as revealed by electron and laser scanning confocal microscopy. The cement contains extractable calcium and magnesium,and non-extractable phosphorus. Amino acid analysis demonstrated that the phosphorus is in the form of phosphoserine and that >90% of seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
270
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(284 citation statements)
references
References 24 publications
8
270
0
6
Order By: Relevance
“…The cementing material, which adheres sand and shell fragments together, is produced in bilateral glands and secreted from a special organ (Jensen & Morse, 1988). The cement bonds and the whole tubular construction must be strong and stable to withstand the turbulent, high‐energy environment of the intertidal zone (Stewart et al ., 2004). After secretion, the cement appears creamy white or light tan and turns reddish to dark brown as it ages (Jensen & Morse, 1988; Stewart et al ., 2004).…”
Section: Comparison Of Cement With Other Biological Adhesivesmentioning
confidence: 99%
See 3 more Smart Citations
“…The cementing material, which adheres sand and shell fragments together, is produced in bilateral glands and secreted from a special organ (Jensen & Morse, 1988). The cement bonds and the whole tubular construction must be strong and stable to withstand the turbulent, high‐energy environment of the intertidal zone (Stewart et al ., 2004). After secretion, the cement appears creamy white or light tan and turns reddish to dark brown as it ages (Jensen & Morse, 1988; Stewart et al ., 2004).…”
Section: Comparison Of Cement With Other Biological Adhesivesmentioning
confidence: 99%
“…The cement bonds and the whole tubular construction must be strong and stable to withstand the turbulent, high‐energy environment of the intertidal zone (Stewart et al ., 2004). After secretion, the cement appears creamy white or light tan and turns reddish to dark brown as it ages (Jensen & Morse, 1988; Stewart et al ., 2004). It sets in only 30 s, but takes several hours to cure into a solid foam (Stevens et al ., 2007).…”
Section: Comparison Of Cement With Other Biological Adhesivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxylation (e.g., tyrosine to DOPA) and phosphorylation (e.g., serine to phosphoserine) are post‐translational modifications commonly used by marine organisms to modify the adhesive properties of their cement proteins 7, 8, 27, 28, 29. As previously mentioned, barnacle cement does not contain DOPA;10, 11, 12 however, Gohad et al and Dickinson et al demonstrated that cyprid cement and the barnacle cementing apparatus are phosphorylated, respectively 14, 30.…”
mentioning
confidence: 99%